Influence of Milk Ph on the Chemical, Physical and Sensory Properties of a Milk-Based Alcoholic Beverage - Osorio-Lira, F (CAMBRIDGE UNIV PRESS, 2019)
The research reported in this Research Communication evaluates the effect of milk acidification on the physicochemical and sensory properties of Licor de Oro (or Gold Liqueur; LO), a traditional alcoholic beverage produced in Chiloe island, Chile, which is made by mixing milk acidified with lemon juice and alcohol at a ratio of 1.0:1.0, along with sugar and other spices. The mixture is stored for a couple of weeks and then filtered to obtain a product with a yellowish-transparent appearance, sweetness and acidic taste, milky and alcoholic notes. The lack of information regarding LO processing, mainly in the amount of acid added to the mixture, leads to products of highly variable quality. Thus, the objective of this study was to evaluate the effect of milk acidification on the physicochemical and sensory properties of LO. Raw milk was acidified using citric acid to six different pH values: 6.7 (control), 6.0, 5.3, 4.6, 3.9 and 3.2. These milk treatments were then used to make LO. A decrease of milk pH led to LO with higher levels of sensorial and titratable acidity. LO obtained at pH 6.7 and 6.0 had higher levels of total protein than other treatments, leading to excessive turbidity. In contrast, treatments made at pH <= 5.3 had a typical transparent appearance of LO. These results suggest that a minimum level of milk acidification is required to obtain LO with desired appearance and composition.